691 IS OPEN LEFT THORACO-ABDOMINAL ESOPHAGECTOMY A VIABLE OPTION IN THE ERA OF MINIMALLY INVASIVE ESOPHAGECTOMY?. (17th September 2021) - Klevebro, Fredrik; Han, Shiwei; Ash, Stephen; Mueller, C; Cools-Lartigue, Jonathan; Maynard, Nick; Ferri, Lorenzo; Low, Donald
Abstract: : Left thoracoabdominal esophagectomy (LTE) facilitates complete resection of esophageal cancer particularly for bulky tumors, but there are concerns that this approach is associated with significant morbidity. The aim of the current study was to evaluate short-term and oncological outcomes of left thoracoabdominal esophagectomy compared to minimally invasive esophagectomy for cancer of the esophagus and gastroesophageal junction. Methods: Prospectively entered esophagectomy databases from three high volume centers were reviewed for patients undergoing LTE or MIE 2012–2018. Patient demographics, tumour characteristics, operative outcomes, postoperative outcomes, and pathologic surrogates of oncologic efficacy (R0 resection rate, and number of resected lymph nodes) were compared. In total 844 patients were included in the study, LTE was applied in 654 (77.5%) patients, and MIE in 190 (22.5%) patients. Results: LTE patients had more neoadjuvant treatment (LTE = 74.5%, MIE = 64.9%, P = 0.027). There was no difference in overall postoperative complications (LTE = 61.9%, MIE = 64.6%, P = 0.517), severe complications (Clavien Dindo >IIIa (LTE = 26.6%, MIE 26.5%, P = 0.982), pneumonia (LTE = 29.8%, MIE = 26.3%, P = 0.349), anastomotic leak (LTE = 7.7%, MIE = 9.9%, P = 0.348), or in-hospital mortality (LTE = 1.5%, MIE = 2.1%, P = 0.584). Median length of stay was 11 days after LTE vs. 8 days after MIE (P < 0.001). R0 resection rate was 92.4% and 95.6% respectively (P = 0.144). Median number of resected lymph nodes was 25 for LTE and 28 for MIE (P = 0.017). LTE had more node positive resections (LTE = 57.6%, MIE = 44.0%, P = 0.001). Conclusion: LTE was used for tumors with greater lymph node burden in patients that were more likely to have received neoadjuvant treatment compared to MIE. MIE was associated with significantly shorter length of hospital stay, however postoperative morbidity and Clavien-Dindo scores were equal to that of MIE in this cohort.